NF-κB p65 proximity labeling reveals multi-level crosstalk with lysosomal transcription factors TFE3, TFEB, and zinc finger protein GLIS2 - Leib, Lisa; Justus Liebig University Giessen (My University, 2024)
The IL-1α-NF-κB signaling pathway represents a prime example of an inducible transcription factor system and plays a central role in the immune response and cancer. Despite an in-depth understanding of cytosolic signal transduction, little is known about the molecular networks that coordinate gene-specific, spatial and temporal activation of NF-κB-regulated immune genes in the nucleus. In this work, the hypothesis that the NF-κB-dependent function of a cell is modulated by dynamic interaction networks and continuous communication with other subcellular systems was investigated. To this end, two innovative biotin-based pulldown technologies (CAPTURE and MiniTurboID) were used to determine the specific NF-κB interactome in relation to individual inflammatory promoters or the NF-κB subunit p65. While CAPTURE-based purification of individual chromatin loci was experimentally established but ultimately did not lead to the identification of specific factors, MiniTurboID proximity labeling enabled the mapping of the transient and dynamic NF-κB p65 protein interactome. For proximity labeling, p65-deficient cells were reconstituted with a doxycycline-inducible p65-miniTurbo fusion protein or with p65 mutants (E/I or FL/DD), and the biotin-tagged interactors were subsequently identified by affinity proteomics using LC-MS/MS. A comprehensive bioinformatic analysis revealed more than 300 high confidence interactors (HCIs). Most HCIs are of nuclear origin, involved in the regulation of transcription or chromatin processes and require intact p65 dimerization but no DNA binding. A siRNA screen of the top 38 HCIs revealed a regulatory role of TFE3, TFEB and GLIS2 in the inducible expression of three prototypical IL-1α-regulated NF-κB target genes. TFE3 and TFEB are considered master transcription factors regulating the expression of lysosomal CLEAR (coordinated lysosomal expression and regulation) genes, while GLIS2 is a member of the Krüppel-like zinc finger protein subfamily. Prototypic CLEAR genes were expressed independently of p65. In contrast, transcriptome-wide analysis of p65-, TFE3-, TFEB-, TFE3/TFEB- or GLIS2-deficient cells revealed 44 IL-1α-regulated genes that require p65, TFE3 and TFEB for their expression and 83 genes that are cooperatively regulated by p65 and GLIS2. In addition, more than two-thirds of the p65/RELA motifs found among p65 ChIP-seq peaks were closely associated with TFE3 and GLIS2 motifs. Protein interaction maps derived from these data revealed a novel p65-TFE3-TFEB genetic network enriched with multiple components of interleukin signaling pathways and a TNF-centric subnetwork regulated by p65 and GLIS2. In summary, the combined analysis of selected NF-κB p65 interactors at the level of loss-of-function screens, genome-wide mRNA expression and chromatin recruitment revealed a multi-step crosstalk of lysosomal and NF-κB signaling pathways and additionally provided novel insights into critical functions of GLIS2 affecting components of both signaling axes.
Keywords: ddc:570